The company control threshold in Poland after the reform of mandatory takeover bids - Chyla, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
This article is devoted to the problem of mandatory takeover bids in Poland on the grounds of previously binding regulations and the new legal provisions. After many years of waiting by the Polish investors, on 30 May 2022, amendments to the Public Offering Act came into force. They primarily concern changes in the rules regarding conducting mandatory takover bids for the sale or exchange of shares in public companies on a regulated market. The most important change, which also constitutes the main subject of this article’s discussion, is the introduction of the so-called control threshold for companies, at the level of 50%. The aim of this article is to present the former regime on takeover bids as well as to critically analyze the newly adopted one. Moreover, the author gives comparative insight into the matter and criticizes the current Polish regulation as inconsistent with the European law. The paper concludes with a de lege ferenda call for revision of the control threshold under Polish capital market laws in order to ensure investor protection safeguards compliant with the EU law.
Keywords: takeover bids; investor protection; control threshold